A method for preparing small-sized silk fibroin nanoparticles loaded with ligustrazine

By preparing small-size silk fibroin nanomicrospheres loaded with ligustrazine, the existing ligustrazine drug metabolism is solved, the problems of fast half-life, and limited local drug efficacy concentration are achieved, and the sustained and controlled release effects of ligustrazine are improved, and the effect of treating lumbar disc degeneration is improved.

CN119074958BActive Publication Date: 2025-03-04NANJING UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411418134.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-03-04
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing drugs used to treat lumbar disc degeneration have problems such as fast metabolism, short half-life, low bioavailability, and frequent administration of drugs that can easily lead to accumulation poisoning, and the local drug efficacy concentration is limited.

Method used

The preparation method of small-size silk fibroprotein nano-microspheres with ligustrazine-loaded ligustrazine was adopted to prepare nano-microspheres with small particle size and uniform distribution through the mixing of degummed silk and ternary solution, deionized water dialysis, microfluidic droplet in, redissolution and freeze-drying of the mixed solution.

Benefits of technology

The sustained and controlled release effects of ligustrazine are achieved, with good biocompatibility and degradability, improving the delivery efficiency and therapeutic effect of the drug, and reducing the toxic side effects of the drug.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119074958B_ABST
    Figure CN119074958B_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing small-sized silk fibroin nano-microspheres loaded with ligustrazine, and belongs to the field of biomedical technology. The preparation method is as follows: S1, dissolving degummed silk and a ternary solution containing anhydrous calcium chloride, double distilled water and anhydrous ethanol, and then dialyzing with deionized water and removing impurities by centrifugation to obtain a silk fibroin solution; S2, uniformly mixing the silk fibroin solution and the ligustrazine solution to obtain a mixed solution; S3, dropping the mixed solution into acetone by microfluidics, and then standing at room temperature, centrifuging, and discarding the supernatant to obtain a precipitate; S4, re-dissolving the precipitate in deionized water, centrifuging, discarding the supernatant, and repeating 2 to 5 times; finally, re-dissolving in deionized water, filtering and collecting the filtrate to obtain a ligustrazine silk fibroin nano-microsphere solution; S5, freeze-drying the ligustrazine silk fibroin nano-microsphere solution to obtain a silk fibroin nano-microsphere powder loaded with ligustrazine; the prepared silk fibroin nano-microspheres have a small particle size and are evenly distributed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedicine, and in particular relates to a method for preparing small-sized silk fibroin nanoparticles loaded with ligustrazine. Background Art

[0002] Lumbar disc degeneration is a common orthopedic disease that seriously affects the physical and mental health of patients. Among them, the main clinical manifestation of early disc degeneration is disc-related low back pain, which has the most serious and widespread impact. Studies have found that ligustrazine has a certain pharmacodynamic effect on disc degeneration. Currently, ligustrazine hydrochloride and ligustrazine phosphate are mainly used in clinical practice. However, the methyl group in its molecule is easily oxidized and metabolized, and it has the disadvantages of rapid metabolism, short half-life, and low bioavailability. At the same time, frequent administration is required in clinical use, which is easy to cause cumulative poisoning. The effective concentration obtained for blood vessels in local disc tissue is even more limited. Therefore, seeking a minimally invasive / non-invasive targeted intradiscal vascular controlled release delivery method is of clinical significance for significantly improving the persistent treatment effect of pain.

[0003] Silk fibroin is a natural polymer material. It is a structural protein extracted from natural silk protein and is composed of 18 amino acids. It has attracted much attention in the fields of biomedicine and materials science because of its good biocompatibility, biodegradability, low cytotoxicity and non-immunogenicity. It has become a carrier material approved by the US Food and Drug Administration for drug delivery systems. The chemical structure of silk fibroin has the potential for hydrophobic, hydrophilic and charged molecular interactions, which makes it widely used as a carrier for drug delivery. Studies have found that small-sized silk fibroin nanoparticles can pass through the cell barrier and enter the cell, thereby optimizing cell uptake and cell penetration, and improving drug delivery efficiency and therapeutic effects. However, there are still problems such as large particle size, uneven distribution and poor effect of nanoparticles. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a method for preparing small-sized silk fibroin nanoparticles loaded with ligustrazine. The prepared silk fibroin nanoparticles have small particle size, uniform distribution and good sustained release, controlled release and enzyme-like activity effects.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing small-sized silk fibroin nanoparticles loaded with ligustrazine, comprising the following steps:

[0007] S1. The degummed silk was mixed and dissolved with a ternary solution containing anhydrous calcium chloride, double distilled water and anhydrous ethanol, and then dialyzed with deionized water and centrifuged to remove impurities to obtain a silk fibroin solution;

[0008] S2. mixing the silk fibroin solution and the ligustrazine solution to obtain a mixed solution;

[0009] S3. dropping the mixture into acetone by microfluidics, and then standing at room temperature, centrifuging, and discarding the supernatant to obtain a precipitate;

[0010] S4. The precipitate is sequentially re-dissolved in deionized water, centrifuged, and the supernatant is discarded and then repeated 2 to 5 times; finally, the precipitate is re-dissolved in deionized water, and the filtrate is collected by filtration to obtain a solution of ligustrazine silk fibroin nanoparticles;

[0011] S5. freeze-drying the ligustrazine silk fibroin nanosphere solution to obtain ligustrazine-loaded silk fibroin nanosphere powder.

[0012] Preferably, the degummed silk is obtained by degumming mulberry silk by boiling it with alkali solution, washing it with deionized water, and then drying it in a fume hood.

[0013] Preferably, the molar ratio of anhydrous calcium chloride, double distilled water and anhydrous ethanol in the ternary solution in S1 is 1:8-12:1-4.

[0014] Preferably, the concentration of the silk fibroin solution in S1 is 1-5 mg / mL.

[0015] Preferably, the dissolution temperature in S1 is 70-90° C., and the dissolution time is 5-8 hours.

[0016] Preferably, the molecular weight cutoff of the dialysis bag used for dialysis in S1 is 10000-14000Da, and the dialysis time is 2-4 days.

[0017] Preferably, the centrifugal speed in S1 is 1000-1500 rpm / min, and the centrifugal time is 10-30 min.

[0018] Preferably, the concentration of the ligustrazine solution in S2 is 80-150 mg / mL; the mass ratio of silk fibroin to ligustrazine is 1:0.01-0.05.

[0019] Preferably, the mixing in S2 is carried out using a vortex oscillator with a rotation speed of 1000-1200 rpm / min and a mixing time of 30-60 s.

[0020] Preferably, the volume ratio of the mixed solution to acetone in S3 is 1:3-6; the mixed solution is dripped at a speed of 20-30 mL / h by microfluidics. By adopting the above technical solution, the speed and time of microsphere formation can be controlled by dripping the mixed solution by microfluidics, and the contact area of ​​the microspheres can be expanded.

[0021] More preferably, the microfluidic means is specifically: loading the mixed liquid into a syringe and fixing it to a syringe pump; wherein the specification of the syringe is 20 mL, and the height between the syringe needle and the acetone liquid level is 10 to 15 cm.

[0022] Preferably, the standing time in S3 is 15 to 30 min, the centrifugal speed is 4000 to 5500 rpm / min, and the centrifugal time is 1 to 1.5 h.

[0023] Preferably, the centrifugation time in S4 is 10 to 20 minutes; during the deionized water re-dissolution process, an ultrasonic cell crusher is used for ultrasonic treatment, and the ultrasonic parameters are ultrasonic 2 to 4 seconds, stop 2 to 4 seconds, ultrasonic intensity 120 to 650W, and ultrasonic time 16 to 30 seconds. By adopting the above technical solution, multiple deionized water re-dissolutions can effectively remove acetone attached to the microspheres.

[0024] Preferably, the pore size of the filter membrane in S4 is 0.2-0.45 μm.

[0025] Preferably, in the freeze-drying process in S5, the precooling temperature is -40 to -50°C, the precooling time is 2 to 5 hours, the vacuum drying is 20 to 25 hours, and the vacuum degree is 0.1 to 2Pa.

[0026] The present invention also provides the use of the silk fibroin nano-microspheres prepared by the above-mentioned preparation method in a medicine for treating lumbar disc degeneration.

[0027] Contains at least the following beneficial technical effects:

[0028] 1. The present invention loads ligustrazine on silk fibroin nanoparticles by a self-assembly method, so that the microspheres can have an excellent sustained-release effect while taking into account a faster initial release rate and are degradable.

[0029] 2. The present invention loads ligustrazine onto silk fibroin nanospheres by a self-assembly method, and can prepare nanospheres with a particle size of less than 100 nm. Small-sized nanospheres can act on the lesion site alone, and can also be combined with other macromolecular substances to achieve a synergistic effect. The preparation method is simple to implement, has a low production cost, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 TEM images of silk fibroin nanospheres prepared in Examples 1-5 of the present invention and Comparative Example 1; wherein a is a particle size distribution curve of silk fibroin nanospheres loaded with ligustrazine prepared in the present invention; Figure b is Example 1; Figure c is Example 2; Figure d is Example 3; Figure e is Comparative Example 1; Figure f is Example 4; and Figure g is Example 5.

[0031] Figure 2 Figure 1 is a graph showing the biosafety of silk fibroin nanoparticles loaded with ligustrazine prepared at a concentration of 2% for mesenchymal stem cells and macrophages, Figure a / c shows the effect of silk fibroin nanoparticles loaded with ligustrazine at different concentrations on the activity of mouse endothelial cells and macrophages, and Figure b / d shows the live / dead staining of macrophages and endothelial cells under the stimulation of 10 μg / mL ligustrazine-containing silk fibroin nanoparticles.

[0032] Figure 3 The in vitro release diagram of silk fibroin nanoparticles loaded with ligustrazine prepared under different silk fibroin solution concentrations of the present invention.

[0033] Figure 4 This is a diagram of the POD-like enzyme activity of silk fibroin nanospheres loaded with ligustrazine prepared under different silk fibroin solution concentrations of the present invention. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0035] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0036] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the main idea or essential features of the present invention. Therefore, from all points of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any reference numerals in the claims should not be regarded as limiting the claims involved.

[0037] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.

[0038] It should also be understood that the specific embodiments described above are only used to explain the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention, which should be covered by the protection scope of the present invention / invention.

[0039] The degummed silk preparation method used in the following examples is as follows: anhydrous sodium carbonate is dissolved in deionized water to prepare a sodium carbonate solution (0.05%, w / v), then a certain amount of natural silk is added to the sodium carbonate solution (solid: liquid ratio = 1:50), the mixture is heated to 100°C and steamed for 30 minutes, and washed with deionized water, and the above steps are repeated 3 times. Subsequently, the wetted SF is placed in a fume hood to dry to obtain degummed silk.

[0040] Example 1

[0041] This embodiment provides a method for preparing small-sized silk fibroin nanoparticles loaded with ligustrazine, comprising the following steps:

[0042] S1. Add 10.19 g of degummed silk into 2000 mL of a solution containing anhydrous calcium chloride, double distilled water and anhydrous ethanol (the molar ratio of anhydrous calcium chloride, double distilled water and anhydrous ethanol is 1:8:2), and dissolve at 90°C for 6 h; pour the silk fibroin solution into a dialysis bag with a cutoff of 14000 Da, dialyze with deionized water for 3 days, and dilute to obtain a 0.1 wt% silk fibroin solution.

[0043] S2. Add 100 mg / ml ligustrazine solution to the silk fibroin solution obtained in step 1) to make the mass ratio of ligustrazine to silk fibroin solution be 0.05:1, and shake the mixture on a vortex oscillator for 15 seconds; the rotation speed is 1100 rpm / min, and the mixing time is 50 seconds.

[0044] S3. The mixed solution obtained in step 2) is fixed to a syringe pump using a syringe of 20 mL specification and a height of 15 cm between the syringe needle and the acetone liquid surface. The mixed solution is dripped into acetone at a rate of 25 mL / h (the volume ratio of the mixed solution to acetone is 1:3), allowed to stand at room temperature for 15 min, centrifuged at 5000 rpm / min, 4°C for 1 h, and the supernatant is discarded to obtain a precipitate.

[0045] S4. The precipitate was re-dissolved in deionized water, centrifuged for 20 minutes, and the supernatant was discarded; then the precipitate was re-dissolved in deionized water, centrifuged again for 20 minutes, and the supernatant was discarded; finally, the precipitate was re-dissolved in deionized water and filtered through a 0.22 μm filter membrane to collect the filtrate;

[0046] During the re-dissolution process in deionized water, an ultrasonic cell crusher was used for ultrasonic treatment, and the ultrasonic parameters were ultrasonic 3s, stop 3s, ultrasonic intensity of 500W, and ultrasonic time of 25s.

[0047] S5. The filtrate was freeze-dried to obtain silk fibroin nanoparticle powder loaded with ligustrazine. The precooling temperature during the freeze-drying process was -50°C, the precooling time was 3 hours, the vacuum drying was 23 hours, and the vacuum degree was 1.5 Pa.

[0048] Example 2

[0049] The preparation method of this embodiment is the same as that of embodiment 1, except that the concentration of the silk fibroin solution in step S1 is 0.2 wt %.

[0050] Example 3

[0051] The preparation method of this embodiment is the same as that of embodiment 1, except that the concentration of the silk fibroin solution in step S1 is 0.5 wt %.

[0052] Example 4

[0053] The preparation method of this embodiment is the same as that of embodiment 1, except that the concentration of the silk fibroin solution in step S1 is 1 wt %.

[0054] Example 5

[0055] The preparation method of this embodiment is the same as that of embodiment 1, except that the concentration of the silk fibroin solution in step S1 is 1.5 wt %.

[0056] Example 6

[0057] This embodiment provides a method for preparing small-sized silk fibroin nanoparticles loaded with ligustrazine, comprising the following steps:

[0058] S1. 10.19 g of degummed silk was added into 2000 mL of a solution containing anhydrous calcium chloride, deionized water and anhydrous ethanol (the molar ratio of anhydrous calcium chloride, deionized water and anhydrous ethanol was 1:10:3), and dissolved at 80°C for 5 h; the silk fibroin solution was poured into a dialysis bag with a cutoff of 10000 Da, dialyzed with deionized water for 4 days, and diluted to obtain a 0.1 wt% silk fibroin solution;

[0059] S2. A 100 mg / ml ligustrazine solution was added to the silk fibroin solution obtained in step 1) so that the mass ratio of ligustrazine to silk fibroin solution was 0.05:1, and the mixture was shaken by a vortex oscillator for 15 seconds; the speed was 1000 rpm / min, and the mixing time was 30 seconds;

[0060] S3. The mixed solution obtained in step 2) is fixed to a syringe pump using a syringe having a specification of 20 mL and a height of 10 cm between the syringe needle and the acetone liquid level; the mixture is dripped into acetone at a rate of 20 mL / h (the volume ratio of the mixed solution to acetone is 1:5), allowed to stand at room temperature for 20 min, centrifuged at 4000 rpm / min, 4°C for 1.5 h, and the supernatant is discarded to obtain a precipitate;

[0061] S4. The precipitate was re-dissolved in deionized water, centrifuged for 10 minutes, and the supernatant was discarded; then the precipitate was re-dissolved in deionized water, centrifuged again for 10 minutes, and the supernatant was discarded; finally, the precipitate was re-dissolved in deionized water and filtered through a 0.2 μm filter membrane, and the filtrate was collected;

[0062] During the re-dissolution process in deionized water, an ultrasonic cell crusher was used for ultrasonic treatment, and the ultrasonic parameters were ultrasonic 2s, stop 2s, ultrasonic intensity of 120W, and ultrasonic time of 16s.

[0063] S5. The filtrate was freeze-dried to obtain silk fibroin nanoparticle powder loaded with ligustrazine. The precooling temperature during the freeze-drying process was -40°C, the precooling time was 2h, the vacuum drying was 20h, and the vacuum degree was 0.1Pa.

[0064] Example 7

[0065] This embodiment provides a method for preparing small-sized silk fibroin nanoparticles loaded with ligustrazine, comprising the following steps:

[0066] S1. Add 10.19 g of degummed silk into 2000 mL of a solution containing anhydrous calcium chloride, double distilled water and anhydrous ethanol (the molar ratio of anhydrous calcium chloride, double distilled water and anhydrous ethanol is 1:12:4), and dissolve at 70°C for 8 h; pour the silk fibroin solution into a dialysis bag with a cutoff of 12000 Da, dialyze with deionized water for 2 days, and dilute to obtain a 0.1 wt% silk fibroin solution.

[0067] S2. Add 100 mg / ml ligustrazine solution to the silk fibroin solution obtained in step 1) to make the mass ratio of ligustrazine to silk fibroin solution be 0.05:1, and shake the mixture on a vortex oscillator for 15 seconds; the rotation speed is 1000 rpm / min, and the mixing time is 30 seconds.

[0068] S3. The mixed solution obtained in step 2) is fixed to a syringe pump using a syringe of 20 mL specification and a height of 10 cm between the syringe needle and the acetone liquid surface. The mixed solution is dripped into acetone at a rate of 30 mL / h (the volume ratio of the mixed solution to acetone is 1:6), allowed to stand at room temperature for 30 min, centrifuged at 5500 rpm / min, 4°C for 1.5 h, and the supernatant is discarded to obtain a precipitate.

[0069] S4. The precipitate was re-dissolved in deionized water, centrifuged for 20 minutes, and the supernatant was discarded; then the precipitate was re-dissolved in deionized water, centrifuged again for 20 minutes, and the supernatant was discarded; finally, the precipitate was re-dissolved in deionized water and filtered through a 0.45 μm filter membrane to collect the filtrate;

[0070] During the re-dissolution process in deionized water, an ultrasonic cell crusher was used for ultrasonic treatment, and the ultrasonic parameters were ultrasonic 4s, stop 4s, ultrasonic intensity 650W, and ultrasonic time 30s.

[0071] S5. The filtrate was freeze-dried to obtain silk fibroin nanoparticle powder loaded with ligustrazine. The precooling temperature during the freeze-drying process was -50°C, the precooling time was 5 hours, and the vacuum drying was performed for 25 hours at a vacuum degree of 2Pa.

[0072] Comparative Example 1

[0073] The preparation method of this embodiment is the same as that of embodiment 1, except that ligustrazine is not added.

[0074] Comparative Example 2

[0075] This comparative example provides a method for preparing nano-microspheres loaded with ligustrazine-silk fibroin, comprising the following steps:

[0076] 1) Dissolve the degummed silk (10.19 g) in 2000 mL of a solution containing anhydrous calcium chloride, deionized water and anhydrous ethanol (molar ratio 1:8:2), pour the resulting solution into a dialysis bag with a cutoff of 14000 Da, dialyze with deionized water for 3 days, and dilute to obtain a 0.2 wt% silk fibroin solution;

[0077] 2) adding 100 mg / ml ligustrazine solution to the silk fibroin solution obtained in step 1), wherein the mass ratio of ligustrazine to silk fibroin solution is 0.05:1, and the mixture is shaken by a vortex oscillator for 15 seconds;

[0078] 3) The mixed solution obtained in step 2) is directly added to acetone (the volume ratio of the mixed solution to acetone is 1:3), allowed to stand at room temperature for 15 min, and centrifuged at 5000 rpm, 4°C for 1 h; the supernatant is discarded, the mixture is re-dissolved in deionized water, and centrifuged again for 20 min; the deionized water washing is repeated 3 times; the supernatant is discarded, and the liquid is freeze-dried to obtain a silk fibroin nanosphere powder loaded with ligustrazine.

[0079] Test Example 1

[0080] The morphology of the silk fibroin nano-microsphere powders obtained in Examples 1-5 and Comparative Example 2 was observed.

[0081] like Figure 1As shown; Figure a is a particle size distribution diagram of the silk fibroin nanospheres loaded with ligustrazine prepared by the present invention. From Example 1 to Example 5, as the concentration of the silk fibroin solution increases, the particle size distribution of the obtained nanospheres becomes wider, and the particle size increases from 77nm to 260.5nm; the particle size of Example 2 (87.56nm) is significantly smaller than that of Comparative Example 2 (178.9nm) at the same silk fibroin concentration; Figures b, c, d, f, and g are TEM images of the silk fibroin nanospheres loaded with ligustrazine prepared by Examples 1-5 of the present invention, and Figure e is a TEM image of Comparative Example 2. From Figures b, c, d, and f, it can be seen that the particle size of the nanospheres is constantly increasing, and the morphology of the protein microspheres is more regular, and as the concentration increases, the microspheres are easy to agglomerate. At the same silk fibroin concentration, compared with Comparative Example 2, the protein microspheres prepared in Example 2 are more regular.

[0082] Experimental Example 2

[0083] The third generation mouse macrophage or endothelial cell suspension was added to 96-well plates (100 μL / well, about 5×10 3 ), cultured in an incubator at 37°C and 5% CO2 for 24h, then added Example 2 (0, 10, 100, 200, 500, 1000 μg / mL) diluted with culture medium at different concentrations, and continued to culture for 24h. Then slowly added 10 μL of CCK-8 solution respectively to ensure that no bubbles were generated, and continued to incubate in an incubator at 37°C and 5% CO2 for 1h. Finally, placed in an ELISA reader, measured the optical density (OD value) of each well at 450nm, and calculated the cell survival rate according to the following formula, and calculated the mean and standard deviation of each group of parallel samples.

[0084]

[0085] The third generation mouse macrophage or endothelial cell suspension was added to 96-well plates (100 μL / well, about 5×10 3 ), and cultured in an incubator at 37°C and 5% CO2 for 24 hours. According to the concentration of Example 2 determined by the CCK-8 test to be non-toxic to mouse macrophages and endothelial cells, it was diluted with culture medium and added to a 96-well plate, and a control well (silk fibroin nanospheres without ligustrazine loading) was set up to continue culturing for 24 hours. Then, referring to the instructions of the cell live / dead staining Calcein-AM / PI detection kit, a working solution (2μM calcein AM, 8μ M PI) was prepared, the culture medium in the 96-well plate was removed, and washed with PBS, 100μL of the working solution was added, and incubated at room temperature for 30-45 minutes. The effect of SF-LTH on the proliferation ability of the two cells was then observed under a fluorescence microscope.

[0086] Figure 2The present invention prepares the effect of different concentrations of silk fibroin nanoparticles loaded with ligustrazine on the activity of mouse macrophages and endothelial cells. As shown in Figure a, as the concentration of nanoparticles is higher than 100μg / ml, different toxicity is produced on mouse macrophages; as shown in Figure b, as the concentration of nanoparticles is higher than 10μg / ml, endothelial cells are toxic. Live / dead staining of macrophages and endothelial cells under the stimulation of 10μg / ml found that SF-LTH had no effect on the proliferation of the two cells, indicating that silk fibroin nanoparticles loaded with ligustrazine exhibit good biocompatibility.

[0087] Experimental Example 3

[0088] Weigh 10 mg of original drug ligustrazine accurately in a volumetric flask, add PBS to 100 mL, mix evenly, and then use a pipette to accurately draw 250, 500, 750, 1000, 1250, 1500, 1750, 2000, 2250 μL into a 10 mL volumetric flask, and dilute to 10 mL respectively to obtain standard solutions with drug mass concentrations of 2.5, 5, 7.5, 10, 12.5, 15, 17.5, 20, 22.5 mg / L. Take the middle value of 12.5 mg / L and use a UV-visible spectrometer to measure the maximum absorption wavelength of 295 nm. Measure the absorbance value of each group of standard solutions at a wavelength of 295 nm. The linear regression equation of drug concentration-absorbance of ligustrazine in PBS was obtained by fitting the curve. The standard curve equation was: Y=0.0365X+0.0686, and the correlation coefficient R2=0.9802.

[0089] Weigh 50 mg of SF-LTH microspheres and dissolve them in 50 ml of PBS. Maintain the temperature in a constant temperature oscillator at 37°C and 100 r / min for drug release. Pipette 6 mL of sample solution at 1, 2, 4, 8, 12, 24, 48, and 72 h, and add 6 mL of PBS. Measure the absorbance by UV-visible photometer, and calculate the cumulative release percentage of ligustrazine at each time point according to the following formula to explore the drug release characteristics of the drug-loaded microspheres.

[0090]

[0091] Wherein, Vt is the total volume of the drug release medium (mL); Ct is the concentration of the drug in the drug carrier medium at sampling point t (mg / L); Vi is the volume of each sampling (mL); M is the total mass of the drug-loaded microspheres (mg); and A is the drug loading of the drug-loaded microspheres.

[0092] Figure 3The in vitro sustained release diagram of ligustrazine loaded silk protein nano-microspheres prepared by different preparation methods at the same concentration. It can be seen that the small-sized microspheres prepared by the present invention have a drug burst rate reduced from 14.9% to 6.5% compared with the conventionally prepared nano-microspheres, and the drug release rate is also reduced. This shows that the small-sized nano-microspheres are more tightly combined with ligustrazine, which is conducive to prolonging the release time of ligustrazine in vitro, ensuring that ligustrazine continues to play a role in vitro, and reducing the toxic side effects of the drug on the human body.

[0093] Experimental Example 4

[0094] In 1 mL of 0.2 M HAc-NaAc buffer at pH = 3.6, the prepared nanosphere solution, 10 mg / mL of 3,5,3',5'-tetramethylbenzidine (TMB) solution and 30% of H2O2 were added in sequence, so that the reaction system finally contained 50 μg / mL of Comparative Example 1 or Comparative Example 2 or Example 2, 0.5 mg / mL of TMB solution and 1 M H2O2, and a UV-visible spectrophotometer was used to record the absorbance change curve over time within 1 min at a wavelength of 652 nm. The slope of the curve reflects the initial catalytic rate of the nanoparticles.

[0095] Figure 4 The figure is a diagram of the POD-like enzyme activity of different silk fibroin microspheres; the present invention uses colorless 3,5,3',5'-tetramethylbenzidine (TMB) as a substrate, and can catalyze H2O2 to oxidize TMB to generate a blue product under acidic conditions (pH=3.6) and in the presence of H2O2, and the product has a maximum absorption peak at 652nm. By real-time monitoring the change in absorbance of the reaction solution at 652nm during the reaction, the POD-like enzyme catalysis curves of Comparative Example 1, Comparative Example 2 and Example 2 are obtained. The nano-microspheres prepared by the present invention have excellent POD-like enzyme activity, help to remove peroxides and harmful free radicals, and protect intervertebral disc cells from oxidative damage.

[0096] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing small-sized silk fibroin nanoparticles loaded with ligustrazine, characterized in that: The following steps are involved: S1. The degummed silk was mixed and dissolved with a ternary solution containing anhydrous calcium chloride, double distilled water and anhydrous ethanol, and then dialyzed with deionized water and centrifuged to remove impurities to obtain a silk fibroin solution; S2. mixing the silk fibroin solution and the ligustrazine solution to obtain a mixed solution; S3. dropping the mixture into acetone by microfluidics, and then standing at room temperature, centrifuging, and discarding the supernatant to obtain a precipitate; S4. The precipitate is sequentially re-dissolved in deionized water, centrifuged, and the supernatant is discarded and then repeated 2 to 5 times; finally, the precipitate is re-dissolved in deionized water, and the filtrate is collected by filtration to obtain a solution of ligustrazine silk fibroin nanoparticles; S5. freeze-drying the ligustrazine silk fibroin nanosphere solution to obtain ligustrazine-loaded silk fibroin nanosphere powder; The concentration of the silk fibroin solution in S1 is 1-5 mg / mL; The concentration of the ligustrazine solution in S2 is 80-150 mg / mL; the mass ratio of silk fibroin to ligustrazine is 1:0.01-0.05; The volume ratio of the mixed solution to acetone in S3 is 1:3-6; the mixed solution is dripped at a speed of 20-30 mL / h through microfluidics; In S3, the standing time is 15 to 30 minutes, the centrifugal speed is 4000 to 5500 rpm / min, and the centrifugal time is 1 to 1.5 hours; During the deionized water re-dissolution process in S4, an ultrasonic cell crusher is used for ultrasonic treatment, and the ultrasonic parameters are ultrasonic 2 to 4 seconds, stop 2 to 4 seconds, ultrasonic intensity 120 to 650W, and ultrasonic time 16 to 30 seconds; The centrifugation time in S4 is 10 to 20 minutes; the pore size of the filter membrane is 0.2 to 0.45 μm.

2. The preparation method according to claim 1, characterized in that: The molar ratio of anhydrous calcium chloride, double distilled water and anhydrous ethanol in the ternary solution in S1 is 1:8-12:1-4.

3. The preparation method according to claim 1, characterized in that: The molecular weight cutoff of the dialysis bag used for dialysis in S1 is 10000-14000Da, and the dialysis time is 2-4 days.

4. Use of the silk fibroin nanoparticles prepared by the preparation method according to any one of claims 1 to 3 in preparing a drug for treating lumbar disc degeneration.

Citation Information

Patent Citations

  • Tetramethylpyrazine derivatives modified silk fibroin protein fiber anti-coagulant material and its preparation method

    CN101053661A

  • Preparation methods of ligustrazine nanoparticle solution and spraying agent thereof

    CN102319180A